FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN K4 IBU HAMIL DI WILAYAH KERJA PUSKESMAS LIMA KAUM I KABUPATEN TANAH DATAR TAHUN 2019 - Febriyeni Febriyeni; Thalia Putri Damayanti (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
In Indonesia in 2015, maternal mortality and infant mortality rates are relatively high (305 / 100,000KH and 32 / 1.000KH). In realizing the target of Sustaibanble Development Goals (SDGs) in 2030, the government seeks that every pregnant woman may access quality health services through visits of K1 to K4. This study aimed to determine some factors related to K4 visits of pregnant women in the Lima Kaum I Community Health Center.This study was an analytical design with a cross sectional study. It was conducted on February to March 2019 in Lima Kaum Community Health Center. The populations were 320 pregnant women. Then, accidental sampling technique had been used to take the samples. There were 76 third trimester pregnant women were chosen as the samples of this research.Univariate analysis obtained that there were 52.6% of the respondents did K4 visits incompletely. Then, 59.2% of them had good knowledge. After that, 50% of them had difficult access to health services. Then, there were 77.6% of the respondents exposed to information media. Moreover, bivariate analysis found that t some related to K4 visits were knowledge (p value = 0.004 and OR = 4.735), information media (p value = 0.002 and OR = 10.200) and the factor was not related to K4 visits was health services (p value = 0.818). Based on the results of the study, it can be concluded that there was a relationship between knowledge and information media toward K4 visits. Then, it is expected to pregnant women to check their health services starting from visits K1 to K4. Keywords : Knowledge, Health Care Access, Media Information, K4 Visit